2003
DOI: 10.1002/ejoc.200390130
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Scheme for the Preparation of 13C‐Labeled 3,4‐Didehydro‐Retinal, 3‐Hydroxyretinal, and 4‐Hydroxyretinal up to Uniform 13C‐Enrichment

Abstract: A modular synthetic scheme has been developed for the synthesis of 13 C-labeled naturally occurring visual pigment chromophores; 3,4-didehydroretinal, 3-hydroxyretinal, and 4-hydroxyretinal. These compounds can now be made with Ͼ 99%13 C enrichment at any position or combination of positions. We used the common C 10 +C 5 +C 5 scheme for the syn-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…The [4,4΄-13 C 2 ]-and the other isotopologues of astaxanthin indicated in Scheme 9 have been prepared. In Scheme 10 it is shown that (4RS)-4hydroxy-β-cyclocitronitrile 42 is converted by acid catalyzed dehydration into the cyclohexadienenitrile 51 (van Wijk et al, 2003). Oxidation with m-CPBA acid results epoxidation of 3,4-double bond in product 52.…”
Section: Scheme 8 Preparation Of the End Group Of Canthaxanthin In Amentioning
confidence: 99%
“…The [4,4΄-13 C 2 ]-and the other isotopologues of astaxanthin indicated in Scheme 9 have been prepared. In Scheme 10 it is shown that (4RS)-4hydroxy-β-cyclocitronitrile 42 is converted by acid catalyzed dehydration into the cyclohexadienenitrile 51 (van Wijk et al, 2003). Oxidation with m-CPBA acid results epoxidation of 3,4-double bond in product 52.…”
Section: Scheme 8 Preparation Of the End Group Of Canthaxanthin In Amentioning
confidence: 99%
“…Besides 11- Z retinal in some animals (11 Z )-3,4-didehydroretinal, (3 R )-(11 Z )-3-hydroxyretinal and (4 R )-(11 Z )-4-hydroxyretinal are the chromophores of the visual pigment. The reactions depicted in the synthetic route in Scheme 18 are used for the preparation of above mentioned retinals [ 13 ]. α-Cyclocitronitrile 72 ( Scheme 17 and Scheme 18 ) is used as the starting material in which the double bond can easily be converted into an epoxide ring and subsequent treatment with a base gives ( R/S )-4-hydroxy unsaturated nitrile 73 .…”
Section: Isotope Enriched Chemically Modified Retinalsmentioning
confidence: 99%
“…Only in the case of amphibians and fresh water fish (11 Z )-3,4-didehydroretinal (also known as vitamin A 2 aldehyde) forms the chromophore. In some flies and insects the chromophore is (3R)-(11 Z )-3-hydroxyretinal and in squid it is (4 R )-(11 Z )-4-hydroxyretinal [ 13 , 14 ].…”
Section: Part a Introductionmentioning
confidence: 99%
“…The spectral data of this compound were identical with those of the literature. 21 (2E,4E)-3-Methyl-5-(2,6,6-trimethyl-1,3-cyclohexadienyl)-2,4-pentadienal (10) To a solution of the nitrile 9 (244 mg, 1.14 mmol) in anhydrous dichloromethane (5 ml) was added a solution of DIBAL-H (1.0 M in hexane, 1.26 ml, 1.26 mmol) at 0°C and the resulting mixture was stirred for an additional 30 min. The reaction was quenched with moist silica gel (SiO 2 : H 2 O 5 : 1) and the resulting mixture was stirred for an additional 1 h. After filtration through Celite, the filtrate was dried over sodium sulfate.…”
Section: E4e)-3-methyl-5-(266-trimethyl-13-cyclohexadienyl)-24-mentioning
confidence: 99%
“…The spectral data of this compound were identical with those of the literature. 21 9-(2,6,6-trimethyl-1,3-cyclohexadien-1-yl)-2,4,6,8-nonatetraenenitrile (13) To a stirred suspension of NaH (60% oil dispersion, 18 mg, 0.45 mmol) in THF (5 ml) was added a solution of diphenyl phosphonate (11) (150 mg, 0.48 mmol) in THF (3 ml) was added at 0°C, and the resulting mixture was stirred for an additional 30 min. To this January 2008 113…”
Section: E4e)-3-methyl-5-(266-trimethyl-13-cyclohexadienyl)-24-mentioning
confidence: 99%